Implementasi Sistem Tracking Posisi Ambulans pada Smart Dispatcher Menggunakan Metode Komunikasi Publish/Subscribe - Farah Nabilla Putri Irzan; Dany Primanita Kartikasari; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Ambulance is a vehicle equipped with medical equipment to transport sick person or accident victims. Ambulance tracking is needed to determine the location of the ambulance. Therefore ambulance tracking system is built to track the location of the ambulance. In this system an android application is used to send ambulance data, a web server to receive ambulance data and an android application for patients. Ambulance entity sends data to the data receiver center to store the location of the ambulances and find nearest ambulance to the patient. Data transmission between data sender and the data receiver used publish/subscribe communication method. The results of accuracy testing of distance determination with haversine formula is 99.88810212129279 and the average error is 0.1118978787072161%. The response time for sending data from the publisher to the subscriber has an average time of 880.2 milliseconds. Response time sending requests from the patient's android application to the web server with 1000 ambulance data in the database has an average response time of 70.06666667 milliseconds, 2000 ambulance data has an average response time of 109.6206897 milliseconds, 3000 ambulance data has an average the average response time was 143.7 milliseconds, 4000 ambulance data had an average response time of 187.9666667 milliseconds, and 5000 ambulance data had an average response time of 238.2 milliseconds.